Design of a thermoelectric cooling module for an X-ray detector - Prybyla, A.V. (Journal of Thermoelectricity, 2019)
The paper presents the results of designing a thermoelectric multistage thermoelectric cooling module for X-ray detectors. The structure of a thermoelectric cooler as part of an X-ray detector is developed and the possibilities of its practical use are analyzed. Bibl. 12, Fig. 2.